The fundamentals of surgical instruments : a practical guide to their recognition, use and care - Moutrey, Steve (TFM Publishing Ltd., 2017)
This book provides a sound introduction to surgical instrumentation, including their recognition, use and care. It provides useful information that is essential for operating department practitioners, nurses, scrub practitioners, surgeons under training, surgical technologists, junior doctors and medical students. Descriptions of how and where the instruments are used will also aid in the knowledge required for their application, providing an understanding of instruments for specific procedures. The book is relevant to surgical practice around the world. It also aligns with the core curriculum of the Association of Surgical Technologists in the United States. This book provides the fundamental knowledge required for students and qualified staff working within the perioperative environment, to ensure the safe and efficient use of surgical instrumentation and ultimately the care of the surgical patient as a result. Excerpts from some reviews: "I am impressed by Steve Moutrey's writing style, which is clear, direct, and succinct ... [His] experience as a practitioner and educator is evident in his writing. As a former surgical technology educator and author of similar texts, I can attest to the difficulty of presenting entry-level surgical instrumentation. Mr. Moutrey offers a simplified discussion enhanced with relevant illustrations that will reduce any confusion ..." Jon Paul Price, BSOE MBA Healthcare Education Advisor/Consultant Former CEO, Accreditation Review Committee for Surgical Technology/Surgical Assisting, USA Former CEO, National Board for Surgical Technology and Surgical Assisting, USA "This text is a clearly written guide to the concept of surgical instrumentation, aimed at both pre- and post- registration students within the perioperative environment ... The wealth of illustrations support the text and should prepare the reader for the practicalities of instrument identification and handling. ... I would highly recommend [the book] for all perioperative students who wish to gain a comprehensive introduction to surgical instrumentation." Roger King, BA Cert. Ed Pg Cert (Res) RODP Senior Lecturer/ODP Course Leader University of West London, UK "This book is aimed primarily at the scrub practitioner ... It will also prove to be a useful text for other professions ... including nurses, medical students, surgeons in training and others requiring fundamental knowledge of surgical instrumentation. It describes in pictures and words the basic surgical instrumentation that will be found in all operating theatres ..., allowing easy and instant recognition of a large number of instruments ... This book will be a most welcome and helpful tool ..." Steve Barker, MB BS BSc MS FRCS Consultant Vascular and General Surgeon Royal South Hants Hospital, Southampton, UK "The book covers various types of surgical instruments in current use and the various specialties these instruments are designed for ... Steve Moutrey has drawn upon his vast knowledge and experience both in field hospitals with the military and also from his time within the static theatre environment in the NHS and private sector. It will prove to be a valuable teaching and learning tool to all who read it." Terry Pugh, FAETC IOSH RODP Theatre Clinical Manager Queen Alexandra Hospital, Portsmouth, UK